A utilização da técnica de miografia por bioimpedância elétrica durante para avaliação de força e do metabolismo muscular em atividades sem indução de fadiga - Coutinho, André Brand Bezerra (2020)
The electrical impedance myography is a technique able to assess the passive electrical features of the muscle tissue. The major use of this technique is in the clinic field and in the assessment of unhealthy muscle, although it emerges also as a potential instrumentation to assess the muscle contraction. The literature does not present a deep discussion about physiological and biochemical mechanism of the muscle that could be pointed as the source of muscle impedance changes. When a muscle contraction occurs, the muscle needs some energetic molecules to allow this contraction. These molecules are called ATP and are synthetized through energetic systems. Each system has different biochemical processes and its predominance in ATP synthesis may come up changes in electrical features of muscle tissue. In order to assess each energetic system influence on bioimpedance signal a specific instrumentation was developed to acquire, synchronously and online, the impedance and force data on gatrocnemius of Wistar rats submitted to muscle contractions evoked by electrical stimulation. The animals were submitted to two protocols: the first tried to assess EIM changes during ten short-term muscle contractions with different intensities; the second assessed EIM features during submaximal contraction (30% of maximal force) lasting 100 s and tried to associate EIM and the energetic systems. The results show a significant correlation (r = 0.76) between EIM and exerted force. Moreover, suggest that EIM variations in the second protocol may be associated to ATP supply rates from energetic systems. Then, the EIM system designed at present study, introduce itself as a potential tool for muscular metabolism during exercise.